Polystyrene micro- and nano-particle coexposure injures fetal thalamus by inducing ROS-mediated cell apoptosis. (August 2022) - Yang, Diqi; Zhu, Jiandi; Zhou, Xiaoshu; Pan, Di; Nan, Sha; Yin, Ruiling; Lei, Qianghui; Ma, Ning; Zhu, Hongmei; Chen, Jianguo; Han, Li; Ding, Mingxing; et al.
Graphical abstract: Highlights: PS nanoparticles infiltrated into the fetal thalamus via blood-placenta barrier. PS NPs and carboxyl-modified NPs induced DEGs enriched in oxidative phosphorylation and GABAergic synapse. PS particles during gestation led to anxiety-like behavior of progenies and their GABA levels reduction. Glutathione supplementation prevented excessive ROS and apoptosis in N2A and JEG3. Abstract: The adverse effects of plastic on adult animal and human health have been receiving increasing attention. However, its potential toxicity to fetuses has not been fully elucidated. Herein, biodistribution of polystyrene (PS) particles was determined after the maternal mice were orally given PS micro- and/or nano-particles with and without surface modifications during gestational days 1 to 17. The results showed that PS microplastics (MPs) and nanoparticles (NPs) mainly emerged in the alimentary tract, brain, uterus, and placenta in maternal mice, and only the latter infiltrated into the fetal thalamus. PS NPs and carboxyl-modified NPs induced differentially expressed genes mainly enriched in oxidative phosphorylation and GABAergic synapse. Maternal administration of PS particles during gestation led to anxiety-like behavior of the progenies and their γ-aminobutyric acid (GABA) reduction in the prefrontal cortex and amygdala at Week 8. N-Acetylcysteine (NAC), an antioxidant, alleviated PS particles-induced oxidative injury in the fetal brain and rescued the anxiety-like behavior of the progenies. Additionally, PS nanoparticles caused excessive ROS and apoptosis in neuronal cell lines, which were prevented by glutathione supplementation. These results suggested that PS particles produced a negative effect on fetuses by inducing oxidative injury and suppressing GABA synthesis in their brain. The findings contribute to estimating the risk for PS particles to human and animal health.